Educational Careers and Social Space: A precarious relationship? - Friebel, Harry (Momentum Quarterly, 2013)
The formal openness of compulsory and tertiary education in most European countries stands in stark contrast to the observation that the very same educational systems, which allegedly offers everyone a free choice to pursue and develop his or her strongest talents, contributes significantly ot the maintenance of social inequality and enforces existing social hierarchies. In this context this paper argues that the „Lebenswelt“ of individuals is an important transmission belt for converting existing economic inequalities into unequal educational outcomes. We can try to understand the „Lebenswelt“ of specific individuals by identifying their social background via analyzing the local embeddedness of these individuals. The theoretical and empirical arguments presented in this paper strongly indicate that this kind of local embeddedness has a strong a strong influence on an individual’s general view of the world and thereby also on individual conceptions of education as well as one’s educational aspirations. This relation eventually stabilizes the connection between economic inequality and unequal educational achievements by understanding locality and social embeddedness as a main factor influencing individual educational careers.